Bixin Combined with Metformin Ameliorates Insulin Resistance and Antioxidant Defenses in Obese Mice - Pinheiro, Camila Graça [UNESP] (2024)
Bixin (C25H30O4; 394.51 g/mol) is the main apocarotenoid found in annatto seeds. It has a 25-carbon open chain structure with a methyl ester group and carboxylic acid. Bixin increases the expression of antioxidant enzymes, which may be interesting for counteracting oxidative stress. This study investigated whether bixin-rich annatto extract combined with metformin was able to improve the disturbances observed in high-fat diet (HFD)-induced obesity in mice, with an emphasis on markers of oxidative damage and antioxidant defenses. HFD-fed mice were treated for 8 weeks with metformin (50 mg/kg) plus bixin-rich annatto extract (5.5 and 11 mg/kg). This study assessed glucose tolerance, insulin sensitivity, lipid profile and paraoxonase 1 (PON-1) activity in plasma, fluorescent AGEs (advanced glycation end products), TBARSs (thiobarbituric acid-reactive substances), and the activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) in the liver and kidneys. Treatment with bixin plus metformin decreased body weight gain, improved insulin sensitivity, and decreased AGEs and TBARSs in the plasma, liver, and kidneys. Bixin plus metformin increased the activities of PON-1, SOD, CAT, and GSH-Px. Bixin combined with metformin improved the endogenous antioxidant defenses in the obese mice, showing that this combined therapy may have the potential to contrast the metabolic complications resulting from oxidative stress.